Ritual scalp shaving-a risk factor for community acquired late onset neonatal sepsis - Sen, S; Mondal, KB; Roy, A; Kumar, N; Pant, P; Chatterjee, A (Journal of College of Medical Sciences-Nepal, 2014)
Background Neonatal sepsis is one of the major causes of morbidity and mortality at the community and hospital levels in India. There are several community practices associated with and contributing to Neonatal sepsis, especially late onset variety. Objective To analyze whether scalp shaving is an independent risk factor associated with community acquired late onset neonatal sepsis and the causative organism responsible. Methods This was a prospective, non-interventional, observational study. The study was conducted at two tertiary teaching hospitals in Eastern India from 1st May 2010 to 30th April 2011. A total of 382 babies were diagnosed as Late Onset Neonatal Sepsis and 410 , age and sex matched controls were taken from the Well Baby and Immunization clinics. The patients were clinically screened for sepsis and "septic screen" and blood, urine and CSF cultures sent, as needed. Results History of scalp shaving was present in 46(12.04%) out of 382 cases of Late Onset Neonatal Sepsis as compared to 20(4.87%) of 410 matched community controls, the difference was statistically significant (p<0.005). Positive blood cultures were obtained in 20(43.48%) out of 46 scalp shaven babies as compared to 118(35.11%) out of 336 non scalp shaven babies. The commonest organism in babies with scalp shaving was found to be methicillin resistant Staphylococcus aureus(MRSA), whereas the most common organism in non scalp shaven babies was Klebsiella pnuemoniae. Conclusion Scalp shaving appears to be an independent variable associated with community acquired Late Onset Neonatal Sepsis. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 35-44